Use of two transcription starts in the G6PD gene of the bark beetle Ips typographus - Doleželová, Eva; Žurovec, Michal; Böhmová, M; Sehnal, František (Insect molecular biology, 2006)
The enzyme glucose-6-phosphate dehydrogenase (G6PD) of the bark beetle Ips typographus is derived from a gene that includes eight exons and spans over 7100 nucleotides (nt). By means of two transcription starts, the gene generates two mRNA isoforms that are present in similar amounts in the larvae, pupae and adults. The A isoform includes exon IA of 115 nt, which is followed by intron 1a extending to position 3457 of the gene. The B mRNA isoform begins with exon IB (100 nt) that occupies positions 3291-3390 within the 1a intron. Exons II to VII are included in both mRNA isoforms. The gene contains 31.6% (36.5% in the translated region) of the GC nucleotides. Two transcription starts and the exon/intron organization distinguish bark beetle G6PD from the homologous genes known in other insects. Two enzyme variants were detected in the protein extracts of individual bark beetles but their relationship to the A and B mRNA isoforms is uncertain.
Keywords: regulace genové exprese enzymů; vývojová regulace genové exprese; sekvence nukleotidů; Southernův blotting; Gene Expression Regulation, Enzymologic; RNA, Messenger; Evolution, Molecular; Coleoptera; komplementární DNA; konzervovaná sekvence; Amino Acid Sequence; zvířata; messenger RNA; Transcription Initiation Site; Blotting, Southern; ženské pohlaví; genom hmyzu; DNA, Complementary; hmyzí geny; počátek transkripce; financování organizované; Conserved Sequence; Female; mužské pohlaví; Molecular Sequence Data; molekulární evoluce; Sequence Analysis, DNA; Financing, Organized; Genes, Insect; sekvence aminokyselin; molekulární sekvence - údaje; Glucosephosphate Dehydrogenase; sekvenční analýza DNA; glukosa-6-fosfátdehydrogenasa; brouci; Animals; Male; Genome, Insect; Base Sequence; Gene Expression Regulation, Developmental